The National Golf Foundation Top 100 Businesses in Golf: Investigating the Portfolio Returns vs the Market Portfolio - Willey, Thomas; Robideaux, Douglas (Archives of Business Research, 2021)
In early 2018, the National Golf Foundation (NGF) presented their inaugural list of the top 100 businesses in the approximately $70 billion golf industry. Six sectors of the U.S. Economy are represented by the following breakdown of companies: Equipment (22 firms); Turf and Course Supplies (18); Apparel and Accessories (13); Course Management (13); Media/Technology and Associations, Retail and Other (23). The purpose of our research is to determine if an investor could generate above-market returns by investing in a portfolio of the publicly traded firms that are part of this initial list. Our results, indicate that over the entire sample period, three golf related stocks outperformed the overall market index after adjusting for risk.